EFFECT OF ADDITION OF DIFFERENT NITRATE CONCENTRATION ON Spirulina platensis BIOMASS WITH SEMI OUTDOOR SYSTEM - Natalia, Natalia; Amin, Bintal; Effendi, Irwan (Asian Journal of Aquatic Sciences, 2019)
Spirulina platensis is one type of microalgae that has high nutrient and protein content and can live in fresh and marine waters. In the growth of S. platensis requires several supporting factors in its growth period, one of which is nitrate (NO3). Nitrate is needed in the formation of proteins and amino acids in cells and also helps in increasing biomass. This study was conducted with the aim to see the effect of adding different nitrate concentrations to S. platensis biomass with a semi-outdoor system. This research was conducted in March-April 2019 using the experimental method. Water quality parameters during the study obtained in the form of temperatures ranging from 29 – 30oC, pH 9 and salinity 25 ppt. The optimum nitrate concentration for the growth of S. platensis was at a concentration of 9 ppm with a total biomass of 0.669 grams.